2015
DOI: 10.1111/acem.12629
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Needle‐free Jet Injection System With Buffered Lidocaine Device Does Not Change Intravenous Placement Success in Children in the Emergency Department

Abstract: Objective Needle Free Jet Injection system with buffered lidocaine (J tip) has been shown to reduce pain for intravenous line (IV) insertion, but its relationship with successful IV placement has not been well studied. This study aimed to determine if J tip use is associated with improved first attempt IV placement success in children Methods This was a retrospective cohort study of children ages 1 to 18 years with emergent IV placement. Approximately 300 children were selected from each of three separate ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Resistance toward implementation at the individual staff and unit level presented challenges during the rollout process. We found that the key to overcoming this resistance was providing necessary resources, support, and training to staff: “The new way had to be easier than the old way.” When we could demonstrate that wait times went down instead of up (as often anticipated by staff); that topical anesthetics did not decrease the chance of venous cannulation (there was not a single report of venous constriction impeding cannulation, confirming published data 38 , 48 ); and—most importantly—that the 4 strategies provided an immediate benefit to patients (eg, fewer tears; more calm and cooperative children), the Comfort Promise was embraced by nearly all staff. The Lean Value Stream process involves regular process audits, implementation of knowledge translation strategies, 76 development of educational and outreach materials (see supplemental figure for an example, available at http://links.lww.com/PR9/A24 ), and utilization of PDSA cycles.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Resistance toward implementation at the individual staff and unit level presented challenges during the rollout process. We found that the key to overcoming this resistance was providing necessary resources, support, and training to staff: “The new way had to be easier than the old way.” When we could demonstrate that wait times went down instead of up (as often anticipated by staff); that topical anesthetics did not decrease the chance of venous cannulation (there was not a single report of venous constriction impeding cannulation, confirming published data 38 , 48 ); and—most importantly—that the 4 strategies provided an immediate benefit to patients (eg, fewer tears; more calm and cooperative children), the Comfort Promise was embraced by nearly all staff. The Lean Value Stream process involves regular process audits, implementation of knowledge translation strategies, 76 development of educational and outreach materials (see supplemental figure for an example, available at http://links.lww.com/PR9/A24 ), and utilization of PDSA cycles.…”
Section: Discussionmentioning
confidence: 54%
“…Children and their parents/legal guardians had the option of declining any or all strategies, which included the following 14 : (1) “Numb the skin” (for children of 36-week corrected gestational age and older). We chose to use 4% lidocaine cream 63 or needle-less lidocaine application using a J-tip (sterile, single-use, disposable injector that uses pressurized gas to propel medication through the skin) 38 , 39 as topical anesthetics. (2) Sucrose 20 , 54 or breastfeeding 51 for infants 0 to 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a needlefree jet injection of 1 % buffered lidocaine prior to needle procedures also seems promising and provides analgesia in less than a minute. It was shown to be superior to topical anesthetics or vapocoolant in some RCTs but not to jet placebo [122][123][124].…”
Section: Topical Anestheticsmentioning
confidence: 99%
“…This large-scale initiative was the first of its kind worldwide to mandate offering 4 evidence-based practices for needle procedures to all patients (topical anesthetics, sucrose and/or breastfeeding [for infants], comfort positioning, and distraction). [26][27][28][29][30][31][32][33][34][35] After rollout in the outpatient laboratories in 2014 (30 000 children annually) and the medicalsurgical units, the remainder of the inpatient units, including all critical care areas, joined the campaign in 2015. At the time the current study was conducted, all inpatient units had implemented the initiative, but were in various stages of adoption.…”
mentioning
confidence: 99%